2002
DOI: 10.1353/hub.2003.0002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against a Relationship between Dermatoglyphic Asymmetry and Male Sexual Orientation

Abstract: Hall and Kimura (1994) studied the relation between dermatoglyphic asymmetry and male sexual orientation in a sample of 66 homosexual and 182 heterosexual men. They found that more homosexual men possessed a leftward dermatoglyphic asymmetry than did heterosexual men. In this paper, we report a comparative study about the relationship between sexual orientation and dermatoglyphic characteristics, including 60 homosexual men, 76 heterosexual men, and 60 heterosexual women, recruited from the general population,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…However, data from several other recent reports congruently suggest that this sex effect might indeed be quite small. For example, based on 60 male and 60 female Brazilian heterosexual adults (Forastieri et al, 2002;calculated from their For the sake of completeness as well as for comparative purposes, the present study in addition followed the dataanalytic approach of the two prior related studies (Daly et al, 2008;Manning, 2002), that is, combined-sex analyses were also conducted. These supplemental tests likewise yielded no reliably and consistently negative associations between the 2D:4D ratio and finger-ridge counts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, data from several other recent reports congruently suggest that this sex effect might indeed be quite small. For example, based on 60 male and 60 female Brazilian heterosexual adults (Forastieri et al, 2002;calculated from their For the sake of completeness as well as for comparative purposes, the present study in addition followed the dataanalytic approach of the two prior related studies (Daly et al, 2008;Manning, 2002), that is, combined-sex analyses were also conducted. These supplemental tests likewise yielded no reliably and consistently negative associations between the 2D:4D ratio and finger-ridge counts.…”
Section: Discussionmentioning
confidence: 99%
“…However, data from several other recent reports congruently suggest that this sex effect might indeed be quite small. For example, based on 60 male and 60 female Brazilian heterosexual adults (Forastieri et al, 2002;calculated from their Kimura and Carson (1995) observed a sex effect for TFRC of d ¼ .37 in their sample of 154 male and 96 female Canadian undergraduates.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual orientation. In men, fingerprint asymmetry was found to be associated with sexual orientation in one study, with homosexual men found to have the femaletypical LOR pattern more often than heterosexual men [272], but this was not replicated in two studies of homosexual men [273,274] or in two studies of transsexual men [275,276]. In women, fingerprint asymmetry has not been found to relate to sexual orientation, with two studies failing to find differences between homosexual and heterosexual women [234,274].…”
Section: Introductionmentioning
confidence: 99%
“…If sexual orientation is influenced by prenatal perturbations, then people expressingahomosexualphenotypeshouldalsoshowmarkers of elevated DI (i.e., increased left handedness and greater levels of FA). Previous studies using dermatoglyphic asymmetry and somatic asymmetry of the hands (finger length) have revealed null results (Forastieri et al, 2002;Mustanski et al, 2002a). This may suggest that the time period in which digits develop prenatally may not coincide well with a critical period for brain development related to sexual orientation.…”
Section: Introductionmentioning
confidence: 97%